DC solar systems in off-grid applications, technical-economic study in relation to AC solar systems - Leiva, Álvaro; Rivas, Gustavo (EASI: Engineering and Applied Sciences in Industry, 2023)
Electricity access is currently considered a basic service; however, for geographical or economic reasons, in certain regions network distribution becomes unviable. Thus, systems applying renewable energy emerge as a solution, with off-grid solar energy being notable among them. Nevertheless, these are still expensive and energy-inefficient systems, since they depend on various DC/AC and AC/DC conversions to power domestic loads, generally AC, a process in which a large part of the energy generated is lost. The proposed off grid solar system (OGH) is based on the direct use of DC, to efficiently harness photovoltaic solar energy. With this solution, the minimum power demand for the photovoltaic system was reduced by 15%, and consequently the value of the investment decreased by 20.3%, in relation to conventional systems.